THE EFFECT OF BEAUTY INFLUENCER, LIFESTYLE, BRAND IMAGE AND HALAL LABELIZATION TOWARDS HALAL COSMETICAL PURCHASING DECISIONS - Alfitri Zukhrufani; Muhammad Zakiy (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2019)
This study aims to determine the effect of beauty influencers, lifestyle, brand image and halal labelling on purchasing decisions for halal cosmetics. In this study using a quantitative method with cross sectional analysis. The variable measurement scale is done using a likert scale. The sample in this study was a student of Muhammadiyah Yogyakarta University who used halal cosmetics and had read or watched videos about cosmetics from a Beauty Influencer. The number of samples collected and successfully analyzed as many as 226 of the 242 respondents taken by using purposive sampling technique. The object of analysis in this study is halal cosmetic products. The analytical method used is multiple regression analysis. The results of this study show that the beauty influencer, lifestyle, brand image and labelling halal have a positive effect on purchasing decisions of halal cosmetics.